Old George Orwell got it backward : some thoughts on behavioral tax economics - Joel Slemrod (Center for Economic Studies and ifo Institute (CESifo), 2009)
It is entirely appropriate that the study of public finance take seriously behavioral inconsistencies with traditional models of individual and collective decision-making. This raises the question of whether the state should play a role in protecting individuals from themselves, and whether individuals are susceptible to manipulation, or even exploitation, by the people who comprise the state. In this essay I address one aspect of this issue how it affects an economic analysis of tax systems. In addressing this task I ask, and offer some tentative answers to, what is distinctive about behavioral tax economics as a sub-field of behavioral economics and as a sub-field of tax economics.
Keywords: H20; H27; 330; complexity; compliance; Steuersystem; Steuermoral; Verhaltensökonomik; Theorie